Geochemical reactions initiated by subglacial abrasion of natural quartz and alkali feldspar - Gill-Olivas, Beatriz; Telling, Jon; Tranter, Martyn (Frontiers in Earth Science, 2024)
The role of subglacial abrasion in sustaining subglacial microbiomes is an area of growing interest. It is likely that subglacial abrasion produces a range of bio-utilisable compounds, some released from fluid inclusions in the confines of the mineral matrix and some produced via the surface free radicals that crushing produces in a variety of different minerals. As yet, the geochemical reactions which are initiated by abrasion remain poorly understood. This is largely because of the multiple potential sources and sinks of free radicals that occur in even the most simple of multi-mineralic system during crushing and subsequent wetting of the mixture. We illustrate this assertion by conducting a series of laboratory experiments where common, "simple" silicate minerals, such as quartz and feldspar, are abraded and incubated with ultra-pure water. Gaseous reaction products included CH4, H2 and CO2. The concentrations of major ions (including Na + , K + , Mg 2+ and Ca 2+ ), dissolved silicate, dissolved iron and pH of the solution during incubation are reported. These results were used to calculate HCO3 -in solution and the saturation index with respect to various minerals using PHREEQCi. We found that abrasion of silicates produces bio-available gases and has the potential to increase the concentration of various weathering products in solution. Further, we found that even trace amounts of carbonates, an impurity in many natural rocks and minerals, may significantly affect the reaction products, making it challenging to concretize the reactions taking place. These results highlight the importance of conducting abrasion experiments utilising natural samples to better understand how apparently negligeable changes in mineralogy might affect the reaction products of abrasion and crushing.